Sustainable aquaculture development in sub-Saharan Africa - Ragasa, Catherine; Charo-Karisa, Harrison; Rurangwa, Eugene; Nhuong Tran; Shikuku, Kelvin Mashisia (Springer, 2022)
Aquaculture must grow above the current rate of 11% per year to meet projected demand and reduce dependence on seafood imports. Government support and private investment are urgently needed for sustainable growth.